Mass-employment and occupational health and safety: enforcement of standards and can disasters be avoided? - Hashim, A. H. (2016)
The Occupational Safety and Health Act has been in force since 1994 to safeguard workers from occupational accidents but the sheer number of labour force makes it a tremendous challenge for DOSH to ensure employers compliance. Are we heading towards potential industrial disaster?